The effect of biorhythm cycles on the athletic achievement among 400m sprinters - Nacer Youcef (sports creativity, 2025)
This research aims to uncover the impact of biorhythm cycles on athletic performance. We achieved this by analyzing the various physical, psychological, and mental biorhythms of world-class 400m runners and their relationship to the dates of their best athletic results. Based on the records of the International Association of Athletics Federations (IAAF), we obtained data on a sample of 50 male senior athletes with the highest performance records, representing approximately 30% of the total population. We then analyzed their biorhythms and correlated them with the dates of their athletic achievements, leading to the following conclusions: • Biorhythms, with their various physical, psychological, and mental cycles, influence the performance of 400m runners, with optimal results achieved during the positive phase of each cycle. • The impact of biorhythm cycles varies among athletes from one sport to another.